Dukungan Keluarga dan Efikasi Diri Mempengaruhi Hasil Belajar Biologi Peserta Didik Kelas XI SMA Negeri 24 Bone - Hasmatang Hasmatang; Irwandi Rahmat; Rezki Rezki (Universitas Negeri Makassar, 2023)
This research is descriptive research that is correlational in nature and aims to determine the relationship between family support and self-efficacy with students' biology learning outcomes. The population of this study was 94 students in class XI MIPA SMA Negeri 24 Bone. The sample for this study was 62 people, taken using proportional random sampling technique. Data collection was carried out in January of the 2019/2020 academic year. Data on family support and self- efficacy were collected using questionnaires and data on biology learning outcomes were obtained from biology learning outcomes tests in the form of multiple choice questions. Research data was analyzed using descriptive statistics to determine family support, self-efficacy and students' biology learning outcomes, as well as inferential statistics, namely normality tests using the Kolmogrov-Smirnov test, linearity tests using ANOVA Table analysis, and simple correlation tests using Pearson Product Moment and regression tests, to determine the relationship and contribution of family support and self-efficacy variables to students' biology learning outcomes. The results of the research show that: 1) dominant students have moderate category family support with a percentage of 33.87%, 2) dominant students have moderate category self-efficacy with a percentage of 35.48%, 3) dominant students have learning outcomes biology is in the very high category with a percentage of 35.48%, 4) there is a positive and significant relationship between family support and students' biology learning outcomes in the low relationship category, 5) there is a positive and significant relationship between self-efficacy and students' biology learning outcomes students with a low relationship category, 6) there is a positive and significant relationship between family support and self-efficacy together with the biology learning outcomes of students with a medium relationship category.